2007
DOI: 10.1002/ajmg.a.31669
|View full text |Cite
|
Sign up to set email alerts
|

Spinal extradural arachnoid cysts associated with distichiasis and lymphedema

Abstract: Spinal extradural arachnoid cysts (SEDAC) are lesions communicating to the subarachnoid space of the spinal canal via a dural defect. SEDAC occupies intraspinal space and sometimes causes neurological disturbances. Although most reported cases are sporadic, several familial cases have been described, suggesting a genetic etiology. Here we report on a family with SEDAC inherited in an autosomal dominant mode. Detailed study showed that the family has the lymphedema-distichiasis syndrome. Among family members ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The same Q100X truncating mutation was found in one of the families reported by Erickson et al, 4 but SEDACs were not looked for. Yabuki et al, 3 however, determined presence of SEDACs but not the molecular nature of the mutation involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The same Q100X truncating mutation was found in one of the families reported by Erickson et al, 4 but SEDACs were not looked for. Yabuki et al, 3 however, determined presence of SEDACs but not the molecular nature of the mutation involved.…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Observations of SEDACs have been occasionally reported in families with LDS. 3,4,8,10 -12 However, the prevalence of SEDACs in LDS subjects is unclear because only one study 3 has included systematic determination of their presence by spinal MRI. In the family we describe here, seven of 12 (58%) members have SEDACs; Yabuki et al 3 reported a prevalence rate of 70%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiography can show compression of the related pedicle bones, enlargement of the spinal canal, and increase in the anteroposterior and pedicle distance. Enhanced CT and myelography also have diagnostic value in SEACs, but MRI is the best choice (16,17,21).…”
Section: Diagnosismentioning
confidence: 99%